449 HYPERTROPHIC CARDIOMYOPATHY: A CASE OF CHALLENGING ARRHYTHMIC RISK STRATIFICATION. (15th December 2022) - Belleggia, Sara; Coraducci, Francesca; Torselletti, Lorenzo; Coretti, Francesca; Paolini, Federico; Alfieri, Michele; Bastianoni, Gianmarco; Brugiatelli, Leonardo; Principi, Samuele; Ciliberti, Guseppe; Barbarossa, Alessandro; Stronati, Giulia; et al.
Abstract: Hypertrophic cardiomyopathy (HCM) is a common disease, mostly inherited, with a prevalence of 1:500. Cornerstone of the clinical management of HCM patients is stratifying the risk of sudden cardiac death (SCD) which is the most frightening complication despite its relatively low incidence (0, 9% per year). Although mathematical risk scores, as proposed by ESC, are the most used to assess the probability of arrhythmic complications leading to SCD, they have been associated with low sensitivity, precluding some high-risk patients from prophylactic ICD implantation. Among the tools at clinicians' disposal for risk stratification in HCM patients, the latest AHA/ACC guidelines propose an "individual risk markers strategy", based on the presence of ≥1 clinical feature such as a family history of SCD, extreme left ventricular hypertrophy (LVH), unexplained recent syncope, NSVT, late gadolinium enhancement (LGE) at CMR, systolic dysfunction and LV apical aneurysm. We present a case that lets us reflect on arrhythmic risk stratification. P.C. is a 58 y.o. male with a history of septal hypertrophy (19 mm) and T wave inversion but without an established diagnosis of HCM. He did not have any familiar history of syncope or SCD. He came to the emergency department for epistaxis and was admitted to the cardiology unit due to the previously mentioned findings, where he underwent cardiac-CTA and CMR showing myocardial bridge of left anterior descending artery, LVH with apical aneurysm and LGE areas localized on the apex (transmural) and on the interventricular septum (subendocardial). No signs of dynamic LVOT obstruction or atrial enlargement emerged from echocardiography. During the observation, asymptomatic NSVT were recorded on continuous ECG monitoring. According to the ESC risk prediction score (3.7%) ICD was not strictly indicated but considering the CMR high-risk profile (according to the suggestions of AHA/ACC) we proposed an ICD implantation anyways. The patient refused any invasive procedure and was implanted with a loop recorder. At 12 months remote monitoring showed a single episode of self-terminated sustained polymorphic ventricular tachycardia (02:23 mm: ss) symptomatic of pre-syncope. The patient was then immediately reached and admitted for ICD implantation in secondary prevention. According to the patient's will, and the no need for bradycardia therapy, an S-ICD was implanted. Figure 1 LV apical aneurysm at CMR Figure 2 Remote Monitoring